Clinging performance on natural substrates predicts habitat use in anoles and geckos. (6th October 2021) - Wright, Amber N.; Kennedy‐Gold, Stevie R.; Naylor, Emily R.; Screen, Robyn M.; Piantoni, Carla; Higham, Timothy E.
Abstract: For arboreal lizards, the ability to cling or adhere to the substrate is critical for locomotion during prey capture, predator escape, thermoregulation and social interactions. Thus, selection on traits related to clinging is likely strong. Correlations between morphology, performance and habitat use have been documented in arboreal lizards, providing a framework for using functional traits to predict habitat use in the field. We tested the hypothesis that clinging performance predicts habitat use in an actively assembling community of introduced lizards in Hawaiʻi comprised of anoles ( Anolis carolinensis, A. sagrei ) and day geckos ( Phelsuma laticauda ). We measured morphological traits (toepad area and lamellae number) and tested clinging performance on two artificial and eight natural substrates in the laboratory. We measured habitat use in 10 m × 10 m outdoor enclosures where habitat availability was controlled and the lizard species assemblage was manipulated to reflect all species combinations. The enclosure experiment generated more than 9, 000 habitat use observations from 360 lizards. Morphological traits that predict performance in Anolis were not predictive in Phelsuma, indicating that direct measures of performance are necessary for comparisons between the genera. Measuring clinging performance on multiple substrates provided key insights into patterns of habitat use. While all three species performed best on an artificial smooth substrate (acrylic), performance on natural substrates predicted which texture (rough vs. smooth) was most often used by each species. Performance predicted perch height use: species with the greatest clinging performance ( A. carolinensis and P. laticauda ) across substrates perched twice as high as A. sagrei . We did not observe habitat shifts in the height or texture of perches used by any species in response to experimental manipulation of the lizard species assemblage. Our results highlight the inextricable link between ecology, morphology and performance, the importance of measuring functional traits in ecologically relevant ways, and the potential for resource partitioning to be influenced by differences in the ability to attach to different substrates. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Resumen: En lagartos arborícolas, la habilidad de adherirse al sustrato es fundamental para capturar presas, huir de depredadores, termorregular e interactuar entre individuos. Por eso es probable que este rasgo esté permanentemente bajo fuerte selección. Correlaciones entre la morfología, el desempeño y el uso de hábitat en lagartos arborícolas han sido documentadas, proporcionando un marco teórico en el cual rasgos funcionales pueden predecir el uso de hábitat en la naturaleza. Testamos la hipótesis de que el desempeño de adherencia en diferentes substratos predice el uso de hábitat en comunidades activas de lagartos introducidos en Hawai'i formadas por Anolis carolinensis, A. sagrei y el gecko diurno, Phelsuma laticauda . Medimos rasgos morfológicos (área de la almohadilla dactilares y número de laminillas) y testamos la capacidad de adherencia en dos sustratos artificiales y ocho naturales. Calculamos el uso de hábitat en recintos al aire libre de 10 × 10 m donde controlamos la disponibilidad de hábitats y manipulamos diferentes conjuntos de especies considerando las posibles combinaciones. El experimento incluyó 360 lagartijas y generó más de 9, 000 observaciones. Los rasgos morfológicos predictivos de desempeño en Anolis fueron diferentes a los de Phelsuma, lo que indica la necesidad de mediciones directas para comparaciones entre géneros. El desempeño en diferentes substratos reveló diferentes patrones de uso del hábitat. Si bien las tres especies se desempeñaron mejor en un sustrato artificial liso (acrílico), el desempeño en substratos naturales predijo qué textura (rugosa vs. suave) seria la más utilizada por cada especie. El desempeño también predijo la altura del hábitat utilizado: las especies con mayor capacidad de adherencia ( A. carolinensis y P. laticauda ) fueron encontradas en ambientes dos veces mas altos que A. sagrei . El uso de hábitat en relación a la altura o textura de los substratos utilizados por la cada especie fue similar independiente de las diferentes combinaciones de especies. Nuestros resultados destacan la complejidad de la relación entre la ecología, la morfología y el desempeño, la importancia de seleccionar rasgos funcionales relevantes según el contexto biológico y cómo diferencias en el desempeño puede influenciar potencialmente la partición de recursos. A free Plain Language Summary can be found within the Supporting Information of this article.